EFFECT OF AUDIT FIRM SIZE AND AUDIT TENURE ON AUDIT QUALITY OF SELECTED LISTED FIRMS IN NIGERIA (Journal of Global Accounting, 2022)
The collapse and demise of companies with highly rated market status in both developed and developing countries has made stakeholders to raise questions about factors that affect audit reporting especially in Nigeria. This study examines the effect of audit firm size and audit tenure on audit quality of selected listed non-financial firms in Nigeria. The study anchors on theory of rational expectations because it emphasizes that duties and responsibilities of the auditors are derived from the confidence and trust that the public bestowed on the success of the audit and the assurance given by the auditor. The study adopts ex post facto research design. As at 31st December 2020, ninety - five (95) non-financial firms were listed on the Nigerian Exchange Group floor. The study used purposive sampling technique to select a sample size of 67 listed non-financial firms in Nigeria. Outcome of the analysis conducted in the study showed that audit firm size has a significant and positive effect on audit quality of the sampled firms while auditors’ tenure has a positive but insignificant effect on audit quality of the sampled non-financial firms listed on the Nigerian Exchange Group. Since audit firm size has significant positive effect on audit quality, the study recommends that small audit firms should be encouraged to be more diligent in their audit assignment while the big four audit firms should sustain quality of their audit report.
Keywords: Audit firm size; Audit quality; Audit tenure; Nigerian Exchange group; Non financial firms